FACTORS AFFECTING CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE: A PANEL DATA STUDY OF INDONESIAN LISTED FIRMS (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2021)
This paper investigates corporate social responsibility disclosure in Indonesia. Specifically, we examine whether profitability and leverage affect the CSR disclosure of companies listed on the Indonesia Stock Exchange. The analytical method used is panel data regression analysis. By examining the 129 companies listed in Indonesia Stock Exchange, we find that there is bothpositive impact of profitability and negative impact of leverage on CSR disclosure significantly. The findings are consistent across one measures of a firm’s profitability (ROA, ROE, and ROI) and one proxies of leverage (DAR and DER). We have successfully contributed to the determinants of CSR disclosure.